Kandungan Mikrob Daging Kelelawar yang Diolah sebagai Bahan Pangan Tradisional MICROBIAL CONTENT IN THE PROCESSED MEAT BATS AS TRADITIONAL FOOD - Tiltje Andretha Ransaleleh; Rarah Ratih Adjie Maheswari; Purwantiningsih Sugita; Wasmen Manalu (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2013)
This study was designed to assess the microbial characteristics of bats meat which were cooked askari and rica-rica, and were stored up to 14 days.The study was divided into two stages, the first stage usedthree types of bat meat that were cooked as rica-rica and kari 14 days after being stored in the refrigerator.The second stage used meat of a species of bat that was cooked as rica-rica and kari a few hours afterslaughtering. The result of the meat analysis at the 1st showd that thetotal count of microbials i.e;Staphylococcus aureus, Escherichia coli, coliform, and Salmonella sp from three species of bats that werecooked rica-rica and kari were above the maximum limit of microbial contaminant occording to BSN(2009). The analysed made on the rica-rica showed that bat meat rica-rica stored up to 14 days containedtotal microbial count of 3,1 x 104 - 6,0 x 104Cfu/mL, Staphylococcus aureus 7,7 x 101- 7,6 x 103 Cfu / mL,Escherichia coli and Salmonella sp was negative. The total microbial count of bat meat kari was 6,8 x 105-9,7 x 105Cfu/mL, Staphylococcus aureus was 4,3 x 101-1 x 104 Cfu /mL. Escherichia coli <3 / mL, andSalmonella sp was negative. Based on the result abtained, it was concluded that the bat meat rica-ricaand kari which were cooked in a few hours after cutting and stored until 14 days were suitable for humanconsumption.